SORGHUM CULTURE INITIAL ESTABLISHMENT BASED ON SOWING MACHINES WORKING SPEED AND FURROWING MECHANISMS: THE INITIAL ESTABLISHMENT OF MAIZE CROPS BASED ON WORKING SPEED AND ON THE FURROWING MECHANISMS OF SOWING MACHINES (Veterinária Notícias, 2021)
The main goal of this article was to evaluate, in field conditions, the performance of the seeder-fertilizer in the initial establishment and the productivity of the Sorghum cultivation, in different work speed and seed deposition height. The experiment was conducted at the Experimental Farm in São Gonçalo dos Campos, located in the municipality of São Gonçalo dos Campos, BA, belonging to the School of Veterinarian Medicine and Animal Science of the Federal University of Bahia - UFBA. It was conducted in a factorial scheme 3x3 in CDR (Completely Randomized Design) or DIC (Delineamento Inteiramente Casualizado) in Portuguese, with 36 experimental unities with three displacement speed, being 4, 6 e 8 km h-1 (1,11, 1,67 e 2,22 m s-1) and three sowing deposition depths (0,01, 0,03 e 0,05 m). The Seed deposition height and plant height were evaluated in 30, 60, and 90 days and the productivity per m2 after 90 days. The work speed didn't demonstrate a significant influence on the analyzed parameters. The adjustment of seed deposition did not establish a significant influence on crop productivity, but it did influence the real seed deposition and plant height in the first two harvests. It concludes that sowing at speeds of 4 to 8 km h-1 and the planting between 0,01 and 0,05m do not influence the productivity of the sorghum crop.  It is recommended to perform the planting at a speed of 8 km h-1 with a depth of 0,05 m.